Closing the Gap Between Urban Planning and Urban Ecology: A South African Perspective - van Zyl, Burné (2021)
Ecological considerations should be an integral part of the decision-making processes of urban planners. Specifically, ecological aspects used in urban ecology, such as green infrastructure and ecosystem services, are substantiated by literature as strategies for improving quality of life, human health, and well-being. Studies dealing with such concepts in the Global South recently gained interest; however, these lack empirical evidence on the integration thereof in mainstream South African urban planning practice. This article conducts a preliminary investigation into the knowledge of ecological aspects of a sample of South African urban planners and their willingness to implement ecological aspects in urban planning practice. The new environmental paradigm scale is employed to determine the environmental worldview (ecocentric or anthropocentric) among respondent and how this relates to their knowledge of ecological aspects. The initial research sample consisted of a total of 283 questionnaires distributed. Although findings of this article are based on a low response rate (15%) of 42 documented responses, it did not affect the validity of the data collected in this context. The initial findings indicated that the environmental worldview of the sample of planners is only one factor influencing their perspective on incorporating ecological considerations. Low to moderate knowledge and awareness regarding ecological aspects such as ecosystem services, green infrastructure, and multi-functionality are argued to be main factors preventing integration in urban planning practice. Findings emphasize the need for context-based implementation strategies and broad recommendations are made for the planning profession as a point of departure to introduce or ingrain ecological considerations.